A GOOD LEADER BASED ON GRADUATING STUDENTS’ DRAWINGS: A SOCIAL REPRESENTATIONS APPROACH - Martikainen, Jari (PEOPLE: International Journal of Social Sciences, 2018)
This research examines graduating students’ conceptions of a good leader and how positive leadership qualities are communicated visually. In order to address this research task, fifteen graduating students in a Finnish upper-secondary vocational college were asked to draw a picture of a good leader and elucidate their drawings verbally. Theoretically, the research draws on the theory of social representations and regards the participants’ drawings as reflecting social representations of leadership among graduating students in Finland. The data were analyzed using content analysis. The results show that students regarded a good leader as approachable, caring, supportive, and responsible, as communicated through an either formal or casual but neat physical appearance. This research provides information on graduating students’ conceptions of leadership. In addition, it shows the important role leaders’ visual nonverbal behavior plays in terms of communicating leadership qualities. The results of this research can provide valuable information for leaders and recruiters on what kinds of assumptions and expectations future employees have of leaders, and what should be taken into consideration when meeting newcomers to the labor market in, for instance, a job interview. In the future, it would be interesting to conduct a similar research with a larger group of participants consisting of students at various levels of education. In addition, it would be interesting to study the conceptions of leadership among students coming from various cultural backgrounds.